2013
DOI: 10.1074/jbc.m112.429316
|View full text |Cite
|
Sign up to set email alerts
|

Selective Induction of Tumor Cell Apoptosis by a Novel P450-mediated Reactive Oxygen Species (ROS) Inducer Methyl 3-(4-Nitrophenyl) Propiolate

Abstract: Background: Generating ROS has become a novel anti-cancer approach. Results: NPP preferentially induces tumor cell apoptosis through P450-catalized ROS production. Conclusion: Cell susceptibility to ROS-induced death is influenced by cellular redox status, p53 mutation, STAT3 activation, and location of ROS production. Significance: Our study not only discovered a novel drug candidate but also shed new light on the understanding of ROS generation and function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
37
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 51 publications
0
37
0
Order By: Relevance
“…S7E), these data revealed that CYP3A5-induced intracellular ROS accumulation may play the key factor for the regulation of mTORC2-ribosome interaction, mTORC2 kinase activity, and mTORC2/p-AKT (S473) signaling. As an important supporting evidence, the GSH/GSSG ratio, which are negatively correlated with ROS level (16)(17)(18), in clinical HCC samples (n ¼ 62, 31 with microvascular invasion named as HM tissues, 31 without microvascular invasion named as LM tissues) were measured and found the remarkably lower GSH/GSSG level in the LM group (Fig. 6H).…”
Section: Cyp3a5-induced Intracellular Ros Enrichment Is Responsible Fmentioning
confidence: 99%
See 2 more Smart Citations
“…S7E), these data revealed that CYP3A5-induced intracellular ROS accumulation may play the key factor for the regulation of mTORC2-ribosome interaction, mTORC2 kinase activity, and mTORC2/p-AKT (S473) signaling. As an important supporting evidence, the GSH/GSSG ratio, which are negatively correlated with ROS level (16)(17)(18), in clinical HCC samples (n ¼ 62, 31 with microvascular invasion named as HM tissues, 31 without microvascular invasion named as LM tissues) were measured and found the remarkably lower GSH/GSSG level in the LM group (Fig. 6H).…”
Section: Cyp3a5-induced Intracellular Ros Enrichment Is Responsible Fmentioning
confidence: 99%
“…These mono-oxygenase reactions depend on electron transfer from NADPH via FAD adrenodoxin reductase and 2Fe-2S adrenodoxin (16)(17)(18). These systems can function as a futile NADPH oxidase, oxidizing NADPH in absence of substrate, and leak electrons via adrenodoxin and P450 to O 2 , producing superoxide and other ROS (16)(17)(18).…”
Section: Cyp3a5-induced Intracellular Ros Enrichment Is Responsible Fmentioning
confidence: 99%
See 1 more Smart Citation
“…AFs form after a series of highly organized oxidation-reduction reactions. Several studies provided evidences indicating that CYP450 enzymes generate superoxide hydrogen peroxide (H 2 O 2 ) as intermediate compounds, and these ROS can cause apoptosis and other cell pathologies [45][46][47]. AFB1 is able to induce ROS generation, which causes oxidative stress.…”
Section: Efects On Oxidative Stress Of Alatoxinmentioning
confidence: 99%
“…The oxidative stress caused by AFB1 may be one of the underlining mechanisms for AFB1-induced cell injury and DNA damage, which eventually lead to tumorigenesis [37]. Studies have revealed that AFB1 alters cell cycle and apoptosis-signaling pathways in liver cell models [43,47,51,52]. AFB1 can cause an increase in ROS formation in animals' target organs including rat liver, duck liver, and mouse lung [37,44,53].…”
Section: Efects On Oxidative Stress Of Alatoxinmentioning
confidence: 99%